PENGGUNAAN MEDIA AUDIO VISUAL PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM UNTUK MENINGKATKAN AKTIVITAS BELAJAR SISWA KELAS V SD N 09 PALEMBANG - Ibrahim, Ibrahim; Pratama, Irja Putra; Sahrim, Sahrim (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang (UIN) Raden Fatah Palembang, 2023)
The aim of this research is to determine the use of Audio Visual Media in Islamic Religious Education Subjects to Improve the Learning Activities of Class V Students of Sd Negeri 09 Palembang in PAI-BP subjects. The model in this research uses Kurt Lewin's research which consists of 4 stages, namely; planning, implementing actions, observing and reflecting. The results of this research can be explained as follows SD Negeri 09 Palembang : a. The use of audio visual media has been proven to improve student learning outcomes in groups. This is demonstrated by the achievement of learning completeness results which reached 88.33%. (first cycle 71.66% to 88.33%). b. The use of audio-visual media can increase teacher activity in the material